MENGKAJI MAKNA KEDEKATAN DAN KEBERSAMAAN ALLAH DENGAN MAKHLUK-NYA DALAM TAFSĪR AL-MISHBĀH - Basrian Basrian (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2021)
Knowing Allah and uniting Him is a concept of monotheism which is called for by the Qur'an and conveyed by the Prophet Muhammad. to his people. Thus it is an obligation for Muslims to study it seriously and deeply. Among the teachings of this monotheism are the verses that inform that Allah is close to His creatures, even Allah Himself is with His creatures wherever they are. These verses and their meanings can cause some Muslims to misunderstand them. Because, the verses seem to state that God is in the heart or God is united or together with His creatures, even God is everywhere. Information on the verse of the Qur'an that mentions Allah is near or Allah is with His servants, of course it cannot be understood simply that Allah is close as close to one thing as another. Or God is one with man as understood by some Sufis. If this is the case, it is clearly contrary to the principles of monotheism taught by the holy Qur'an. To find out what the meaning of the closeness and togetherness of Allah is, this paper tries to trace the answer through M. Quraish Shihab's Tafsīr al-Mishbāh.